Role of concentration fluctuations in metallic glass formation - Ramachandrarao P.; Singh R.N.; Lele S. (My University, 2025)
The glass forming composition range in several binary metallic systems is correlated with the composition dependence of Scc(0), the concentration-concentration fluctuation structure factor at its long wavelength limit. The magnitude of Scc(0) has been evaluated for the liquid phase from available thermodynamic data. It has been observed that Scc(0) exhibits a maximum and tends to the ideal value in the glass forming composition range. Significant and systematic negative deviations from ideal values or the tending to zero of Scc(0) are observed at the stoichiometry corresponding to complexes in the liquid state in the case of compound forming or associated systems. These observations are discussed in terms of the chemical short-range order in the liquid state. It is concluded that while a reasonable degree of order may exist for the compound forming compositions, in the glass forming region itself the liquids are nearly random mixtures of complexes and unassociated component atoms. © 1984.